2020
DOI: 10.1590/1806-9061-2019-1225
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of Major Respiratory Pathogens in Backyard Poultry and their Association with Clinical Disease and Biosecurity

Abstract: Raising backyard birds is a common practice in Brazil, mainly in the countryside or suburban areas. However, the level of respiratory pathogens in these animals is unknown. We sampled two hundred chickens from 19 backyard flocks near commercial poultry farms and performed ELISA to Infectious Bronchitis Virus, avian Metapneumovirus, Mycoplasma synoviae and Mycoplasma gallisepticum. We evaluated the association between the predictive ability of ELISA and Hemagglutination-inhibition (HI)by comparing results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Multiple etiology and complexity are characteristic features of respiratory disease in poultry ( Malik et al, 2004 ; Roussan et al, 2008 ; Mazengia, 2012 ). Among the major pathogens affecting the respiratory tract of chickens worldwide is Newcastle disease virus ( NDV ), infectious laryngotracheitis virus ( ILTV ), infectious bronchitis virus ( IBV ), Mycoplasma gallisepticum ( Mg ), Mycoplasma synoviae ( Ms) , avian metapneumovirus ( aMPV ), avian influenza virus, Pasteurella multocida, Aspergillus fumigatus , and Avibacterium paragallinarum ( Brown Jordan et al, 2018 ; Bhuiyan et al, 2019 ; Batista et al, 2020 ; Swayne, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple etiology and complexity are characteristic features of respiratory disease in poultry ( Malik et al, 2004 ; Roussan et al, 2008 ; Mazengia, 2012 ). Among the major pathogens affecting the respiratory tract of chickens worldwide is Newcastle disease virus ( NDV ), infectious laryngotracheitis virus ( ILTV ), infectious bronchitis virus ( IBV ), Mycoplasma gallisepticum ( Mg ), Mycoplasma synoviae ( Ms) , avian metapneumovirus ( aMPV ), avian influenza virus, Pasteurella multocida, Aspergillus fumigatus , and Avibacterium paragallinarum ( Brown Jordan et al, 2018 ; Bhuiyan et al, 2019 ; Batista et al, 2020 ; Swayne, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the two isolates resistant to the greatest number of drugs were found in carcasses from the semi-backyard system, which does not have a legal definition of production patterns. This type of production specific to some Brazilian geographic regions means that this system does not follow the strict biosafety rules of the industrial system nor the standards defined by law for the backyard system [4,6]. Thus, this scenario may be contributing to the inappropriate use of drugs and the high resistance observed.…”
Section: Discussionmentioning
confidence: 99%
“…The major concern linked to this scenario is the lack of data on the sanitary condition of backyard chickens (e.g. occurrence of zoonotic diseases, monitoring of asymptomatic carriers of zoonotic microorganisms) and the impact they might have on food safety [6][7][8]. Chicken meat is contaminated by pathogenic and spoilage microorganisms during all stages of the production chain [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this study reported that mycoplasmosis control in this region is performed mainly through vaccination and not through biosecurity measures. Batista et al (2020) detected a high seroprevalence for MG, MS, and IBV in backyard chickens raised near commercial farms in the state of Minas Gerais. The presence of these pathogens reinforces that vaccinations protocols should be performed with biosecurity measures to prevent the entry and spread of pathogens in the poultry farms.…”
Section: Detection Of Mycoplasma Synoviae and Other Pathogens In Layi...mentioning
confidence: 91%